Rethinking the local : Adana Kebab and artisanship at the intersection of geography and history - Birbiri, Elif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis focuses on the ‘sense of belonging’ evoked by regional and local cuisines, through the Adana kebab. It explores how ‘local’ cuisines are formed and how they find their place in national cuisines. The thesis is structured around two key foci, namely, the artisanship of the Adana kebab and the process of the standardization of the dish. The first part considers the theoretical framework of the project and offers an alternative perspective on the concept of ‘space’. In addition, it introduces the physical and human geography of the region, its history, and the regional cuisine of Adana. Next, the thesis considers the findings from fieldwork, based primarily upon 28 semistructured interviews conducted with kebab artisans. The fieldwork addresses the dynamics of the regional cuisine around the kebab, in terms of the artisans' experience of craftsmanship, the making of the dish itself- including the ingredients and the equipment involved- and the culture around eating. After engaging with production practices, the thesis takes up a comparative analysis of the consumption patterns of the Adana kebab, both in Adana and Istanbul. Furthermore, the ensuing discussion of the ‘dining out’ culture enables an understanding of the effects of globalization, transformation and standardization of consumption and production practices. The thesis concludes that the experience and understanding of a regional cuisine, and the culture around it, cannot be reduced simply to its taste and smell. On the contrary, it should also involve a consideration of the communal socio-historical memory and cultural sensibilities of the region’s inhabitants.
Keywords: Cooking, Turkish.; Local foods -- Turkey.; Adana Kebab.; Adana Kebap.